Clitics: morphosyntactic alternations. Reflection and didactics (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
In this article we will deal with some morphosyntactic alternations that can occur with unstressed third-person pronouns. Specifically, we will focus on the hesitancy in the use of these pronouns that exists in the Spanish-speaking world, and, especially, in some dialects of the Iberian Peninsula, which causes the phenomena known as leismo, laismo and loismo. For each of the phenomena, we will offer a description of the uses and subtypes, as well as the geographical areas where they are attested according to the bibliography (Fernández Ordóñez, 1993, 1999; NGLE §16.8-16.10, among others). Finally, a brief theoretical discussion of these alternations is included. Theoretical information is complemented with innovative methodology exercises (Bosque, 2015) that encourage the student's linguistic reflection.
Keywords: leismo, laismo, loismo, clitics, teaching